Bronchiolar Adenoma Transforming to Invasive Mucinous Adenocarcinoma: A Case Report - Han, Xu (Onco Targets Ther, 2021)
Bronchiolar adenoma (BA) is recognized as a neoplasm with benign clinical course. Histologically, BA is characterized by nodular proliferation of the bilayered bronchiolar-type epithelium, including multipartite epithelial cells and a continuous layer of basal cells. Recent reports have revealed the frequent presence of driver gene mutations in BA, suggesting its neoplastic nature. However, it is still debatable whether BA has malignant potential. Herein, we report the first case of BA harboring the same KRAS mutation with the adjacent invasive mucinous adenocarcinoma (IMA). Additionally, the loss of continuity of the basal cell layer in the junctional zone between BA and IMA indicated a malignant transformation from BA to IMA in this particular case.